Alterações genéticas relacionadas à obesidade: danos no DNA, perfil de expressão e polimorfismos gênicos - Almeida, Danielle Cristina de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In the last decades, the incidence of overweight and obesity has increased worldwide. Nowadays, obesity is considered by the World Health Organization as a global epidemic with severe consequences that can lead to death. Obesity is a multifactorial disorder which involves different factors such as genetic, environment and life style, and its consequences are not only social or psychological, but are also related to the presence of comorbidities such as hyperthension, type 2 diabetes, heart diseases and many types of cancer. Therefore, obesity control has become a challenge for the human health maintenance, catching the attention of researchers that are trying to understand the mechanisms associated to its development, as well as therapeutical and preventive methods. Based on the information above, the present study aimed to evaluate the association between genetic alterations and obesity, with special focus on the presence of DNA damage, gene expression profiling and genetic polymorphisms. Our study included 300 morbid obese women registered for the bariatric surgery and 300 healthy eutrophic women, matched by age. The comet assay was used to assess primary DNA damage in blood cells; the genetic polymorphisms of ghrelin (GHRL), leptin (LEP) and their receptors (GHSR and LEPR), interleukin-6 (IL-6) and serotonin receptor (5-HT2C) were evaluated by the RT-PCR; gene expression profiling in lymphocytes was assessed by DNA microarrays; and adiponectin (ADIPOQ) and leptin (LEP) gene expression in adipocytes were evaluated by qRT-PCR. Our results showed that the frequencies of GHRL (rs26802), GHRS (rs572169), LEP (rs7799039), LEPR (rs 1137101), IL-6 (rs1800796) and 5-HT2C (rs 3813929) polymorphisms were not different between obese and control groups. However, obese presented higher levels of primary DNA damage (single and double strand breaks, alkali-labile sites and oxidative damage) than eutrophic women, indepedent on ...

Nas últimas décadas, a incidência de indivíduos com sobrepeso ou obesos vem aumentando exponencialmente. Hoje, a obesidade é considerada pela Organização Mundial da Saúde como uma epidemia mundial, com graves consequências que podem levar à morte. A obesidade é uma desordem multifatorial que envolve fatores hereditários, ambiente e estilo de vida, e suas consequências não são apenas sociais ou psicológicas, mas estão principalmente relacionadas à presença de co-morbidades como a hipertensão arterial, diabetes tipo II, doenças cardiovasculares e vários tipos de câncer. Portanto, o controle da obesidade é um desafio para a manutenção da saúde humana, atraindo o interesse de inúmeros pesquisadores que buscam o entendimento dos mecanismos associados ao seu desenvolvimento, bem como novos métodos terapêuticos e de prevenção. Com base nessas premissas, o presente estudo objetivou avaliar a associação entre alterações genéticas e a obesidade, com especial foco para a presença de danos no DNA e para o perfil de expressão e polimorfismos gênicos. A casuística do estudo incluiu 300 mulheres cadastradas na lista de espera para a realização de cirurgia bariátrica e 300 mulheres saudáveis, eutróficas, pareadas por idade. O teste do cometa foi utilizado para avaliação de danos primários no DNA de células sanguíneas; os polimorfismos dos genes da grelina (GHRL)e leptina (LEP)e dos seus receptores (GHSR e LEPR), da interleucina 6(IL-6) e da serotonina (5-HT2C) foram analisados pela técnica de RT-PCR; o perfil de expressão gênica em linfócitos foi avaliado pela metodologia do DNA microarray e a expressão dos genes adiponectina (ADIPOQ) e leptina (LEP) em adipócitos foi avaliada pela técnica de qRT-PCR. Os resultados mostraram que a frequência dos polimorfismos dos genes GHRL(rs26802), GHRS(rs572169), LEP(rs7799039), LEPR(rs 1137101), IL-6 (rs1800796) e 5-HT2C ...
Keywords: Obesidade - Pesquisa; Expressão gênica; Polimorfismo (Genetica); Ensaio cometa; Análise de DNA; DNA - Analysis